MORAL FICTIONS AND MEDICAL ETHICS - Miller, Franklin G. (Bioethics, 2010)
Conventional medical ethics and the law draw a bright line distinguishing the permitted practice of withdrawing life-sustaining treatment from the forbidden practice of active euthanasia by means of a lethal injection. When clinicians justifiably withdraw life-sustaining treatment, they allow patients to die but do not cause, intend, or have moral responsibility for, the patient's death. In contrast, physicians unjustifiably kill patients whenever they intentionally administer a lethal dose of medication. We argue that the differential moral assessment of these two practices is based on a series of moral fictions – motivated false beliefs that erroneously characterize withdrawing life-sustaining treatment in order to bring accepted end-of-life practices in line with the prevailing moral norm that doctors must never kill patients. When these moral fictions are exposed, it becomes apparent that conventional medical ethics relating to end-of-life decisions is radically mistaken.